Assessment Of Conditional Cash Transfer Scheme And Poverty Alleviation Among Rural Poor In Cross River State, Nigeria - Obeten, Ude Bassey; Isokon, Brown Egbe (Advances in Social Sciences Research Journal, 2018)
This study examines the impact of conditional cash transfer scheme on poverty alleviation in the rural communities of Cross River State, Nigeria. The ex-post facto research design was adopted and three hypotheses were formulated in this study. The instrument for data collection was a thirty (30) item structured questionnaire and Focus Group Discussion. The population of the study comprises 2940 beneficiaries of the conditional cash transfer in the eighteen local government areas of the state, from 2010 to 2017. Cluster and simple random sampling techniques were used to select 1176 respondents. The hypotheses were analysed using Pearson product moment correlation. The findings revealed that conditional cash transfer scheme have significant relationship with poverty alleviation in terms of increase school enrolment and had tremendously helped in improving health services utilisation as most of the beneficiaries of this programme were able to access health facilities better than before the scheme. This intervention has equally helped beneficiaries to acquire requisite entrepreneurial skills that helped them to transform their lives and standard of living. On the basis of these findings it is recommended that the government should increase the number of household beneficiaries for wider coverage and spread as well as establish more health facilities in the rural areas. More so, the government should increase the number of people enlisted for entrepreneurial training and skills acquisition. (Word Count 222)